Air pollution-associated blood pressure may be modified by diet among children in Guangzhou, China. Issue 11 (November 2020) - Zhang, Jingshu; Cai, Li; Gui, Zhaohuan; Wang, Suhan; Zeng, Xia; Lai, Lijuan; Lv, Yajie; Tan, Kaiyun; Wang, Hui; Huang, Cunrui; Chen, Yajun
Abstract : Objectives: To assess the associations between long-term air pollution exposure and blood pressure in children, and to explore the modifying effects of diet on prehypertension and hypertension. Methods: We evaluated 7225 primary school children aged 6–12 years from Guangzhou, China, in 2017. The blood pressure was measured objectively. The individual 1-year average concentration of particles with an aerodynamic diameter of 2.5 μm or less or 10 μm or less (PM2.5, PM10 ), sulfur dioxide (SO2 ), and ozone (O3 ) before each blood pressure measurement were calculated by inverse distance weighting interpolation according to each home address. Generalized linear mixed-effects models were used to examine the health effects and potential effect modifications by diet factors after adjusting for covariates. Results: The results showed that the estimated increase in mean SBP was 0.92 mmHg (95% CI 0.05–1.79) per interquartile range increase in O3 . An interquartile range increase in the 1-year mean of SO2 and O3 was associated with odds ratios of 1.26 (95% CI 1.04–1.52) and 1.20 (95% CI 1.06–1.35) for prehypertension, respectively. In addition, an interquartile range increase in PM2.5, SO2, and O3 exposure was positively associated with hypertension, with odds ratios of 1.33 (95% CI 1.11–1.61), 1.70 (95% CI 1.33–2.16), and 1.48 (95% CI 1.20–1.83), respectively. Stronger effect estimates between PM2.5, SO2, and O3 concentration on prehypertension were exhibited among subgroups of children with a higher intake of sugar-sweetened beverages. Conclusion: Long-term exposure to PM2.5, SO2, and O3 were associated with higher blood pressure levels in children, and dietary intake might modify these associations. Abstract : Supplemental Digital Content is available in the text